NEW TECHNOLOGIES IN CRYOSURGERY ENDOSCOPIC TREATMENT OF TUMORS OF THE RESPIRATORY TRACT - V. V. Sokolov; D. V. Sokolov; L. V. Telegina; A. L. Nikolaev; A. P. Kirukhin; Yu. L. Kudryavtseva (Исследования и практика в медицине)
The article presents the history of the development of the cryosurgery method from antiquity to the present day, materials of the clinical use of cryosurgery for endoscopic diagnosis and treatment of tumors of respiratory tract at the present stage, features of modern equipment for cryosurgery. Also the article presents the first clinical experience of using cryorecanalization in stenosing tumors of the tracheobronchial tree inRussiawith the help of the medical device of the latest generation ERBECRYO 2. Three clinical examples of cryorecanalization are given. Preliminary results of clinical studies show that, in comparison with cryosurgery on older devices, cryorecanalization using the latest generation of m edical eq uipment and a new cryosondond model is an effective method of recanalization to restore airway patency, which can be used in combination with electrodestruction, argon-plasma And laser coagulation.